(Im)possibilidade de coletivização da responsabilização de adotantes nos casos de devolução de crianças e adolescentes adotandos e adotados - Joanna Paixao Pinto Rodrigues (2015)
Although adoption is, in Brazilian Law, an irreversible means of placing adoptable children and teenagers in a substitute family, there are cases of return of these children and teenagers, both adoptable and adopted (that is to say, during the adoption process or after it is completed). The discussion about this possibility of return by the adopters (in the case of returning an adoptable) and the parents (in the case of an adopted), loses meaning when the attempt of return is analyzed through the lenses of the childs best interest: one cant leave a child or a teenager in an environment where they are not respected or wanted. After establishing the possibility of actual devolution, there is the need to verify the available means of civil liability for the returners of these children and teenagers. Thus, even though this liability is presently processed by means of a public civil action, the collectivization of these demands is not possible yet, because the Brazilian Law doesnt regulate the passive collective action. The hypothesis initially presented about the possibility of collectivization of the returners liability actions is, therefore, refuted.